Craft Learning at Home: Experiences of learning to make clothes at home using on- and offline resources - Cooke, Sally (FormAkademisk, 2024)
This paper presents findings from a practice-informed, participatory textile craft research study focusing on the experiences of people learning to make clothes for themselves at home. Necessitated by the social distancing restrictions of the Covid-19 pandemic, the study used a combination of journaling and video elicitation methods rather than the in-person workshop-based methodology originally planned for it. While these remote methods limited the community aspect of learning, they also provided an authentic insight into practices undertaken within the home, where both on- and offline resources are used to support learning. The hybrid nature of the research, which involved embodied material craft practices being captured and relayed by participants through digital means, mirrored the way that much contemporary home sewing practice is conveyed. As for other crafts, the popularity of home sewing has been greatly amplified online over the last twenty years. The resurgence of interest in sewing has been associated with a new generation of sewing patterns and instructions as well as a vast array of amateur and professional online content from which sewing beginners glean inspiration, information and instruction. This paper elucidates what happens when sewing beginners encounter these resources and try to make sense of them in material form in relation to their own bodies, skills and material surroundings. The limitations of video in relaying craft practices and the challenges of conveying embodied and tacit knowledge between individuals are highlighted as a result.